2017
DOI: 10.1136/injuryprev-2017-042416
|View full text |Cite
|
Sign up to set email alerts
|

Health system and law enforcement synergies for injury surveillance, control and prevention: a scoping review

Abstract: Background Healthcare providers and law enforcement (LE) officers are among the most common first responders to injuring events. Despite frequent interface between the health system (HS) and LE sectors, the published evidence that supports their collaboration in injury surveillance, control and prevention has not been comprehensively reviewed. Methods We conducted a scoping review of literature published from 1990 to 2016 that focused on local and regional HS and LE collaborations in injury surveillance, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Public health agencies have the authority to receive protected health information and are the ideal partners for receiving, processing and aggregating data from multiple sources. Summary information in the form of aggregate maps and lists of businesses experiencing high counts of violence can then be shared with the community safety partnership for injury prevention and control activities 5 23 24. The Cardiff Model collects, aggregates and shares violence-related injury data, potentially through a public health agency, in a form that may be used by LE and other partners.…”
Section: Discussionmentioning
confidence: 99%
“…Public health agencies have the authority to receive protected health information and are the ideal partners for receiving, processing and aggregating data from multiple sources. Summary information in the form of aggregate maps and lists of businesses experiencing high counts of violence can then be shared with the community safety partnership for injury prevention and control activities 5 23 24. The Cardiff Model collects, aggregates and shares violence-related injury data, potentially through a public health agency, in a form that may be used by LE and other partners.…”
Section: Discussionmentioning
confidence: 99%
“…In the same setting, Maine et al have reported an IPV prevalence of 34.5% in the injured population [ 36 ]. In an effort to curb this problem, a deliberate collaboration between the health care service and law enforcement agencies in injury surveillance and prevention should be promoted [ 37 ]. Further, public health interventions should be designed to identify at-risk populations and key contributing factors for a tailor-made solution in dealing with IPV, especially in this setting [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local police databases may represent important and underutilized resources for describing city-level firearm injury epidemiology 19 20. Partnerships between health systems and law enforcement, like the Cardiff Violence Prevention Program, have the potential to enhance firearm injury surveillance and identify prevention targets 21. Future research in firearm injury epidemiology should use inclusive or linked data sources, including police data, which contain information on both fatal and non-fatal injuries.…”
Section: Discussionmentioning
confidence: 99%